Application of Sulfated Magnetic Nanoparticles in the Synthesis of Biologically Active Ureas - Kuksenok V. Yu. Vera Yurievna; Shtrykova V. V. Viktoriya Viktorovna; Filimonov V. D. Viktor Dmitrievich; Galanov A. I. Andrey Ivanovich (Nanomaterials and Technologies, 2015)
Title screen